APLIKASI TJ TRANSJAKARTA SEBAGAI INSTRUMEN DIGITAL PUBLIC SERVICE DELIVERY: EVALUASI IMPLEMENTASI LAYANAN TRANSPORTASI PUBLIK DIGITAL DALAM PERSPEKTIF NEW PUBLIC SERVICE - Arnis Desgita Eka Putri; Aulia Putri Maharani; Alyssa Nahwa Haura; Fatkhuri Fatkhuri; Maisarah Mitra Adrian (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study critically evaluates the implementation of Digital Public Service Delivery through the Transjakarta TJ (TIJE) application during the 2021–2024 period using the theoretical perspectives of the New Public Service (NPS) and the E-Government Maturity Model.. The primary objective of this research is to analyze the execution of digital-based public transportation services in DKI Jakarta and identify structural barriers to achieving an inclusive, citizen-centric service delivery system. The applied research methodology is qualitative with a case study design under an interpretative-constructivist paradigm. Primary data were collected through in-depth interviews with eight purposively selected informants to represent the diversity of users' demographic backgrounds, including the elderly and visually impaired individuals, supported by documentary studies. The findings reveal a polarization of user experiences where digital natives enjoy high efficiency, while digital immigrants face digital exclusion due to the gradual elimination of physical ticket booths. Furthermore, there is a deficit in NPS principles regarding system inclusiveness and the responsiveness of financial transaction complaints, which are dominated by automated chatbots. In terms of e-government maturity, the TJ app stalls at the transaction stage and has not achieved horizontal cross-modal integration. The digitalization paradox demonstrates that corporate productivity targets often sacrifice the core value of equal basic service delivery. Consequently, this study recommends adopting a hybrid service strategy, designing dedicated features for the elderly, complying with universal accessibility standards, and optimizing human-to-human feedback mechanisms. Keywords: Digital Public Service Delivery, Transjakarta, Digital Inclusivity.